Targeted drug-loaded nano-particles with multiple responsiveness and preparation method of targeted drug-loaded nano-particles
By using polymer nanogel carriers with temperature and pH response characteristics, combining anti-tumor drugs and forming a folic acid layer, the problems of uncontrollable and poor biocompatibility of the existing chemotherapy nanodrug carrier preparation process are solved, and high efficiency and ability are achieved Controlling drug release and targeting effects.
Patent Information
- Application Number
- CN202411177791.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-02-18
AI Technical Summary
The preparation process of existing chemotherapy nanodrug carriers is uncontrollable and complex, has poor biocompatibility and poor stability, and is prone to leaking drugs, making it difficult to achieve multiple stimulus responses.
Poly(N-isopropylacrylamide-copolymer-acrylic acid-copolymer-N-acryloyloxysuccinimide) nanogel with temperature and pH response characteristics was used as a carrier to bind anti-tumor drugs and benigned by amino Folic acid molecules form folic acid layers, enhancing the targeting and multi-responsiveness of the nanoparticles.
The simple and controllable preparation of drug-loaded nanoparticles is achieved, biocompatibility and targeting are improved, and the drug release control is enhanced, especially in the tumor microenvironment, which shows excellent stability and lethality.
Smart Images

Figure BDA0005011206440000021 
Figure BDA0005011206440000022 
Figure BDA0005011206440000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of drug-loaded nanoparticles, and relates to targeted drug-loaded nanoparticles with multiple responsiveness and a preparation method thereof. Background Art
[0002] Cancer has always been one of the most important diseases threatening human health and life. At present, the main means of clinical treatment of cancer include surgical resection, radiotherapy, chemotherapy and targeted therapy. Among them, chemotherapy is one of the most common and effective treatment methods, but it has serious systemic toxic side effects and may cause problems such as drug resistance, which often leads to low tumor treatment efficiency or even treatment failure, seriously damaging the survival and quality of life of patients. Stimuli-responsive nanodrug carriers can respond to endogenous stimuli (such as pH, enzymes, ions or glutathione, etc.) or exogenous stimuli (such as temperature, light, magnetic field, etc.), thereby achieving long-term retention or small-scale release of drugs in normal tissues, and achieving rapid release of drugs in tumor tissues or tumor cells. In overcoming the limitations of traditional chemotherapy, stimuli-responsive nanodrug carriers have shown great potential. However, how to quickly and easily prepare nanodrug carriers with multiple stimulus responses is of great significance for the treatment of cancer.
[0003] Monomers or composite materials with stimulus responsiveness can be used to construct nano drug carriers with multiple responses. According to the different stimulus responsive materials, they can be divided into stimulus responsive liposome nanomaterials, stimulus responsive micelle nanomaterials, stimulus responsive polymer nanochannel materials and stimulus responsive nanogel materials. However, the structures of stimulus responsive liposomes and stimulus responsive micelles are unstable. When the external environment changes, the liposomes and micelles are easily cleaved, resulting in easy leakage of drugs. At the same time, their particle sizes are uneven and difficult to control. In addition, this type of material is also difficult to achieve multiple stimulus responses. When constructing stimulus responsive polymer nanochannel materials, the responsive polymer needs to be grafted into the nanochannel. The synthesis steps are cumbersome and the controllability is poor. Although metal particle-based stimuli-responsive nanogels are a type of flexible nanomaterials with a three-dimensional network structure, they have the characteristics of high drug loading, good colloidal stability, precise and controllable particle size, and easy-to-adjust stimuli-responsive behavior. However, nanomaterials such as precious metal nanoparticles and semiconductor nanomaterials cannot be metabolized by the human body, and long-term retention in the body may cause potential toxicity to the body. In addition, further functional modification of the surface of such stimuli-responsive nanogel carriers is relatively complex and difficult. Although the conjugated structure of pyrrole provides the possibility of surface functionalization of stimuli-responsive nanogels, its degradation behavior in the body is still not fully understood. In addition, pyrrole is unstable in water and easily aggregates, resulting in uncontrollable preparation processes for such stimuli-responsive nanogels. Therefore, there are still challenges in developing stimuli-responsive nanodrug carriers with good biocompatibility and simple and controllable preparation methods. Summary of the invention
[0004] In view of the problems of uncontrollable and complicated preparation process, poor biocompatibility, poor stability, easy drug leakage, etc. of the current chemotherapy nano drug carriers, the present invention provides a targeted drug-loaded nanoparticle with multiple responsiveness and a preparation method thereof, so as to simplify the preparation method of the existing chemotherapy nano drug carriers, increase the controllability of the preparation process, improve the biocompatibility of the existing chemotherapy nano drug carriers and enhance their targeting.
[0005] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:
[0006] The targeted drug-loaded nanoparticles with multiple responsiveness are composed of a poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel with temperature and pH responsiveness, an anti-tumor drug, and a folic acid layer that can specifically target the folate receptor of tumor cells; the anti-tumor drug is loaded in the polymer network structure of the nanogel to form drug-loaded nanoparticles, the folic acid layer is composed of aminated folic acid molecules, the folic acid layer coats the drug-loaded nanoparticles, and the amino groups of the aminated folic acid molecules are grafted on the surface of the drug-loaded nanoparticles; the anti-tumor drug is a hydrophilic or / and positively charged drug, and the structure of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) is as shown in formula (I),
[0007]
[0008] In formula (I), a:b:c:b1=(18~20):(0.8~1.2):(0.8~1.2):(0.8~1.2), a1:b1:c1=(18~20):(0.8~1.2):(0.8~1.2).
[0009] In the technical solution of the above-mentioned targeted drug-loaded nanoparticles with multiple responsiveness, the aminated folic acid molecule is a folic acid-polyethylene glycol-amino group having a structure as shown in formula (II) or a folic acid-fat chain-amino group having a structure as shown in formula (III).
[0010]
[0011] In the above-mentioned technical solution of targeted drug-loaded nanoparticles with multiple responsiveness, in the targeted drug-loaded nanoparticles, the molar ratio of poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel to the folic acid layer is 1:(0.8-1.2).
[0012] In the above technical solution of targeted drug-loaded nanoparticles with multiple responsiveness, the diameter of the targeted drug-loaded nanoparticles in a dry state is 50 to 200 nm.
[0013] In the technical solution of the above-mentioned targeted drug-loaded nanoparticles with multiple responsiveness, the anti-tumor drug is bound to the polymer network structure of the nanogel through electrostatic interaction. For example, when the loaded anti-tumor drug is doxorubicin, the protonated amino group in doxorubicin is bound to the deprotonated carboxyl group in the polymer network of the nanogel through electrostatic interaction under specific pH conditions, so that the doxorubicin is loaded inside the polymer network of the nanogel.
[0014] In the above-mentioned technical solution of targeted drug-loaded nanoparticles with multiple responsiveness, the specific anti-tumor drug used can be determined according to actual application requirements. For example, the anti-tumor drug can be doxorubicin.
[0015] The present invention also provides a method for preparing the above-mentioned targeted drug-loaded nanoparticles with multiple responsiveness, comprising the following steps:
[0016] (1) Preparation of drug-loaded nanoparticles
[0017] The poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is added to a Tris-HCl buffer having a pH value of 8.0 to 8.5, and then an anti-tumor drug is added, and the mixture is fully stirred at room temperature to load the anti-tumor drug into the polymer network of the nanogel, and the mixture is centrifuged, and the obtained solid phase is washed to obtain drug-loaded nanoparticles;
[0018] The structure of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) is shown in formula (I),
[0019]
[0020] In formula (I), a:b:c:b1=(18-20):(0.8-1.2):(0.8-1.2):(0.8-1.2), a1:b1:c1=(18-20):(0.8-1.2):(0.8-1.2);
[0021] (2) Preparation of drug-loaded nanoparticles coated with folic acid
[0022] The aminated folic acid molecules are fully dispersed in a Tris-HCl buffer with a pH value of 8.0 to 8.5 to obtain an aminated folic acid molecule dispersion; the drug-loaded nanoparticles are fully dispersed in a Tris-HCl buffer with a pH value of 8.0 to 8.5 to obtain a drug-loaded nanoparticle dispersion; the drug-loaded nanoparticle dispersion is added dropwise to the aminated folic acid molecule dispersion, fully reacted at room temperature, protected from light and stirred, centrifuged, and the obtained solid phase is washed to obtain the product.
[0023] In step (2) of the technical solution of the above preparation method, the drug-loaded nanoparticle dispersion is preferably added dropwise to the aminated folic acid molecule dispersion in a ratio of 1:(0.8-1.2) of the molar amount of the drug-loaded nanoparticle nanogel to the aminated folic acid molecule.
[0024] Furthermore, in step (2) of the technical solution of the above preparation method, the concentration of the drug-loaded nanoparticle dispersion is preferably 1 to 10 mg / mL, and the concentration of the amino-modified folic acid molecule dispersion is preferably 1 to 10 mg / mL.
[0025] In step (1) of the technical solution of the above preparation method, the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is added to a dispersion formed in a Tris-HCl buffer having a pH value of 8.0 to 8.5, and the concentration of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is preferably 1 to 10 mg / mL.
[0026] In step (1) of the technical solution of the above preparation method, the specific anti-tumor drug used can be determined according to the actual application requirements, and the amount of the anti-tumor drug added is determined according to the drug loading amount of the drug-loaded nanoparticles to be prepared.
[0027] In the technical scheme of the above preparation method, a feasible preparation method of poly (N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is as follows:
[0028] ① Dissolve N-isopropylacrylamide monomer, crosslinking agent N,N'-methylenebisacrylamide, acrylic acid monomer, N-acryloyloxysuccinimide monomer and sodium dodecyl sulfate in water to obtain a reaction precursor solution; after removing oxygen from the reaction precursor solution, add a thermal initiator and react at 70-80°C for 3-4 hours under nitrogen protection;
[0029] In the reaction precursor solution of this step, the concentration of N-isopropylacrylamide monomer is 5-10 mg / mL, the molar ratio of the crosslinking agent, acrylic acid monomer, N-acryloxysuccinimide monomer and N-isopropylacrylamide monomer is (0.8-1.2):(0.8-1):(0.8-1):(0.8-1), the amount of sodium dodecyl sulfate is 3%-5% of the molar amount of N-isopropylacrylamide monomer, and the amount of the thermal initiator is 1%-2% of the molar amount of N-isopropylacrylamide monomer;
[0030] ② Filter the obtained reaction solution, add the filtrate into a dialysis bag, place it in water for sufficient dialysis, and freeze-dry to obtain.
[0031] The present invention is confirmed by experiments:
[0032] (1) The drug-loaded nanoparticles of the present invention were kept in a PBS buffer solution at pH 7.4 and a cell culture medium containing 10% FBS for 7 days, and the particle diameter and Zeta potential remained substantially unchanged, showing excellent stability;
[0033] (2) The drug-loaded nanoparticles of the present invention are pH-responsive and temperature-responsive. When doxorubicin is used as a model drug, the drug-loaded nanoparticles of the present invention have a higher cumulative drug release rate under the condition of pH 5.5 (relative to the condition of pH 7.4). At the same time, the cumulative drug release rate of the drug-loaded nanoparticles of the present invention increases with the increase of temperature; that is, the drug release behavior of the drug-loaded nanoparticles of the present invention is also pH-responsive and temperature-responsive.
[0034] (3) When doxorubicin was used as a model drug, different concentrations of the drug-loaded nanoparticles of the present invention were co-cultured with L929, Hela and 4T1 cells for 72 hours. The growth of L929, Hela and 4T1 cells was very good, and no cell death occurred, indicating that the drug-loaded nanoparticles of the present invention have excellent biocompatibility;
[0035] (4) When doxorubicin was used as a model drug, after 4T1 cells were co-cultured with PNA-DOX nanoparticles without a folate layer and PNA-DOX-FA nanoparticles including a folate layer of the present invention for 3 h, 4T1 cells took up more PNA-DOX-FA nanoparticles of the present invention, that is, the introduction of the folate layer effectively enhanced the targeting ability of the nanoparticles;
[0036] (5) When doxorubicin was used as a model drug, at the same concentration and the same action time, the PNA-DOX-FA nanoparticles of the present invention had a stronger killing effect on 4T1, A549, Hep-G2 and Hela cells than the PNA-DOX nanoparticles that did not include a folic acid layer.
[0037] The principles of the present invention are mainly as follows:
[0038] The preparation method of the present invention first utilizes the interaction between poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel with temperature and pH response characteristics and anti-tumor drugs, and loads the anti-tumor drugs in the polymer network structure of the nanogel to form drug-loaded nanoparticles; then, based on the reaction characteristics between N-acryloyloxysuccinimide in the nanogel and the amino folic acid molecules, a folic acid layer is chemically bonded to the surface of the drug-loaded nanoparticles. Thus, the present invention realizes the simple and controllable preparation of targeted drug-loaded nanoparticles with multiple responsiveness.
[0039] The surface of the targeted drug-loaded nanoparticles with multiple responsiveness of the present invention has a folic acid layer. In tumor treatment, the drug-loaded nanoparticles can actively target tumor cells with overexpression of folic acid receptors and enter tumor cells through endocytosis; based on the polyacrylic acid in the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel network, the nanogel is endowed with pH response characteristics, and the volume phase transition temperature (VPTT) of the nanogel is adjusted to be higher than the normal temperature of the human body. The weakly acidic environment of tumor cells can partially protonate the carboxyl groups in the nanogel network, which not only weakens the electrostatic attraction between the carboxylic acid group and the anti-tumor drug (such as doxorubicin), but also weakens the electrostatic repulsion between the carboxylic acid groups. The protonated carboxyl groups will form hydrogen bonds with the amide groups of the nanogel skeleton, causing the volume of the nanogel to shrink. The weakening of the electrostatic interaction with the drug molecules and the volume shrinkage of the nanogel jointly promote the release of the loaded anti-tumor drug. The temperature of the tumor site is high. When the drug-loaded nanoparticles of the present invention are in the tumor site, the temperature of the drug-loaded nanoparticles will rise. The increased temperature destroys the hydrogen bonding between the amide groups and water molecules in the nanogel network and forms intramolecular hydrogen bonds, causing the nanogel volume to shrink, thereby triggering the explosive release of anti-tumor drugs. The above characteristics make the multi-responsive targeted drug-loaded nanoparticles of the present invention expected to enhance the anti-tumor effect in the chemotherapy treatment of tumors.
[0040] Compared with the prior art, the technical solution provided by the present invention produces the following beneficial technical effects:
[0041] 1. The present invention provides a targeted drug-loaded nanoparticle with multiple responsiveness, which is composed of a poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel, an anti-tumor drug, and a folic acid layer that can specifically target the folate receptor of tumor cells; the anti-tumor drug is loaded in the polymer network structure of the nanogel to form a drug-loaded nanoparticle, the folic acid layer is composed of aminated folic acid molecules, the folic acid layer coats the drug-loaded nanoparticle, and the amino groups of the aminated folic acid molecules are grafted on the surface of the drug-loaded nanoparticle. The folic acid layer introduced on the surface of the drug-loaded nanoparticle can give the drug-loaded nanoparticle the ability to actively target tumor cells with overexpression of folate receptors, and can enter tumor cells through endocytosis. Since the copolymerized poly N-isopropylacrylamide in the nanogel accounts for the vast majority of the nanogel, the nanogel has significant temperature sensitivity. Due to the high temperature at the tumor site, the temperature of the nanogel loaded with anti-tumor drugs increases, thereby destroying the hydrogen bonding between the amide groups and water molecules in the nanogel network and forming intramolecular hydrogen bonds, causing the nanogel volume to shrink, thereby triggering the explosive release of anti-tumor drugs; at the same time, the copolymerized polyacrylic acid in the nanogel gives the nanogel pH response characteristics. As the environmental pH value decreases, the carboxylate groups in the nanogel network are partially protonated, which on the one hand weakens the electrostatic attraction between the carboxylic acid groups and the anti-tumor drugs, and on the other hand weakens the electrostatic repulsion between the carboxylic acid groups. The protonated carboxyl groups will form hydrogen bonds with the amide groups of the gel skeleton, causing the nanogel volume to shrink. The combined effect of these two aspects can promote the release of anti-tumor drugs. That is, after the nano-drug carrier particles of the present invention are targeted and internalized into tumor cells, the weak acid environment and higher temperature of the tumor cells can trigger the release of the anti-tumor drugs loaded in the nano-drug carrier particles, thereby achieving a chemotherapeutic effect on tumor cells. It is expected to be used for chemotherapy treatment of tumors, enrich the types of anti-tumor drug carriers, and enhance the anti-tumor effect.
[0042] 2. The present invention has experimentally confirmed that the drug-loaded nanoparticles of the present invention are kept in a PBS buffer solution at pH 7.4 and a cell culture medium containing 10% FBS for 7 days, and the particle diameter and Zeta potential remain substantially unchanged, and have excellent stability, which can solve the problem of easy drug leakage caused by the structural instability of existing stimulus-responsive liposomes and stimulus-responsive micelles.
[0043] 3. The present invention has experimentally confirmed that after co-culturing L929, Hela and 4T1 cells with different concentrations of the drug-loaded nanoparticles of the present invention for 72 hours, the growth of L929, Hela and 4T1 cells was very good, and no death occurred, indicating that the drug-loaded nanoparticles of the present invention have excellent biocompatibility, which is mainly due to the good biocompatibility and low toxicity of the various raw materials used in the preparation of nanogels of the present invention. Compared with the existing stimuli-responsive drug carriers introduced with precious metal nanoparticles or semiconductor nanomaterials, the drug-loaded nanoparticles of the present invention have better biocompatibility.
[0044] 4. The present invention also provides a method for preparing the above-mentioned targeted drug-loaded nanoparticles with multiple responsiveness. The method firstly uses N-isopropylacrylamide monomer, cross-linking agent N,N'-methylenebisacrylamide, acrylic acid monomer and N-acryloyloxysuccinimide monomer to copolymerize and prepare poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel by precipitation polymerization, then loads the anti-tumor drug on the nanogel, and then grafts the aminated folic acid molecules on the drug-loaded nanoparticles to form a folic acid layer. Since N-isopropylacrylamide and N-acryloyloxysuccinimide are cheap, easy to obtain, and have low toxicity, and acrylic acid is widely present in the daily life environment and also has the characteristics of good biocompatibility, low toxicity, and low cost, the prepared nanogel has the characteristics of good biocompatibility. At the same time, the drug-loaded nanoparticles are easily degraded by enzymes or bacteria in the biological environment in the environment, and are also easily degraded by biological enzymes under physiological conditions, so the synthesis, use and recovery process of the drug-loaded nanoparticles of the present invention are harmless to the environment. In addition, the method of the present invention has a simple process and good controllability, and the surface of the prepared nanogel is easy to modify and functionalize, thereby solving the problems of the uncontrollable preparation process of the existing responsive nano drug carrier, the complicated preparation process, and the difficulty in achieving surface modification and functionalization. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a schematic diagram of the preparation process of PNA-DOX-FA nanoparticles in Example 1.
[0046] Figure 2 Figures a and b are TEM images of PNA nanogel and PNA-DOX-FA nanoparticles in dry state, respectively.
[0047] Figure 3 Figures a and b are the diameter distribution diagrams of PNA nanogel and PNA-DOX-FA nanoparticles in deionized water, pH 5.5 and pH 7.4 PBS buffer, respectively.
[0048] Figure 4It is the infrared spectra of PNA nanogel, PNA-DOX nanoparticles, PNA-DOX-FA nanoparticles and FA-PEG-NH2.
[0049] Figure 5 It is the absorbance curve of DOX, PNA nanogel, PNA-DOX nanoparticles, PNA-DOX-FA nanoparticles and FA-PEG-NH2 in the range of 200 to 800 nm.
[0050] Figure 6 It is FA-PEG-NH2, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles 1 H NMR spectrum.
[0051] Figure 7 is the zeta potential of PNA-DOX-FA nanoparticles in deionized water, PBS buffer at pH 5.5, PBS buffer at pH 7.4, and cell culture medium (Medium) containing 10% FBS.
[0052] Figure 8 The graphs a and b represent PNA nanogels, and the graphs c and d represent PNA-DOX-FA nanoparticles.
[0053] Fig. 9 This is the curve of the change of the hydrodynamic diameter of PNA nanogel, PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles in deionized water with temperature.
[0054] Fig.10 The curves showing the change of the hydrodynamic diameters of PNA nanogels, PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles in PBS buffers at pH 5.5 and pH 7.4 and in cell culture medium (Medium) containing 10% FBS as a function of temperature.
[0055] Fig.11 is the DOX standard curve.
[0056] Fig.12 Figures a and b show the encapsulation efficiency and drug loading test results of PNA-DOX-FA nanoparticles prepared at different DOX concentrations.
[0057] Fig.13These are the drug release curves of PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles in PBS buffer at different pH values and temperatures, where graphs a, b and c represent PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles, respectively.
[0058] Fig.14 These are the fluorescence images of L929, Hela and 4T1 cells co-cultured with PNA-DOX-FA nanoparticles at different concentrations for 72 h.
[0059] Fig.15 are CLSM images of 4T1 cells co-cultured with DOX, PNA-DOX nanoparticles, and PNA-DOXFA nanoparticles for 3 h.
[0060] Fig.16 These are the test results of the inhibitory effects of different concentrations of PNA-DOX nanoparticles and PNA-DOX-FA nanoparticles on different tumor cells. DETAILED DESCRIPTION
[0061] The following examples further illustrate the multi-responsive drug-loaded nanoparticles for tumor chemotherapy and the preparation method thereof. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The technical personnel in the relevant field make some non-essential improvements and adjustments to the present invention based on the above invention content, which still fall within the scope of protection of the present invention.
[0062] Example 1
[0063] In this embodiment, drug-loaded nanoparticles with multiple responsiveness are prepared. The schematic diagram of the preparation process is shown in FIG. Figure 1 As shown, the steps are as follows:
[0064] (1) Preparation of poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel (PNA-NHS nanogel)
[0065] The structural formula of PNA-NHS is shown in the following formula (I):
[0066]
[0067] In formula (I), a:b:c=20:1:1, a1:b1:c1=20:1:1, a:b:c:b1=20:1:1:1.
[0068] ① Add N-isopropylacrylamide (NIPAM) monomer, crosslinker N,N'-methylenebisacrylamide (MBA), acrylic acid (AA) monomer, N-acryloyloxysuccinimide (A-NHS) monomer and sodium dodecyl sulfate (SDS) into a flat-bottom flask, add deionized water and stir until dissolved to obtain a reaction precursor solution; introduce nitrogen for 30 minutes to remove oxygen in the reaction precursor solution; seal the flat-bottom flask and place it in a 70°C water bath, dissolve the initiator potassium persulfate (KPS) in deionized water, and quickly add the KPS aqueous solution into the flat-bottom flask with a syringe under the condition of introducing nitrogen. When the solution in the flat-bottom flask turns light blue, stop introducing nitrogen, quickly seal the flat-bottom flask, and react at 70°C for 4 hours.
[0069] In this step, in the reaction precursor solution, the concentration of NIPAM monomer is 7.06 mg / mL, the molar ratio of MBA, AA monomer, A-NHS monomer and NIPAM monomer is 1:1:1:20, the amount of SDS is 5% of the molar amount of NIPAM monomer, and the amount of KPS is 1.47% of the molar amount of NIPAM monomer.
[0070] ② Take the flat-bottom flask out of the water bath, place it in an ice-water mixture to cool to room temperature, filter it with filter paper to remove agglomerates, add the filtrate into a dialysis bag (MWCO = 100wDa), and dialyze it in deionized water for one week, changing the deionized water twice a day. The product is freeze-dried to obtain PNA-NHS nanogel.
[0071] (2) Preparation of doxorubicin-loaded PNA-NHS nanoparticles (PNA-NHS-DOX nanoparticles)
[0072] Tris (hydroxymethylaminomethane) was dissolved in deionized water to prepare a Tris buffer solution with a concentration of 15 mmol / L, and then the pH value thereof was adjusted to 8.2 with dilute hydrochloric acid to obtain a Tris-HCl buffer solution.
[0073] Add PNA-NHS nanogel to Tris-HCl buffer, stir thoroughly to make PNA-NHS nanogel evenly dispersed, and obtain PNA-NHS nanogel dispersion with a concentration of 0.5 mg / mL. Add doxorubicin to the PNA-NHS nanogel dispersion, stir for 24 hours at room temperature in the dark, then centrifuge at 5000 rpm for 15 minutes using an ultrafiltration tube (MWCO=50 kDa), wash the obtained solid phase 3 times with Tris-HCl buffer, and obtain PNA-NHS-DOX nanoparticles. The obtained PNA-NHS-DOX nanoparticles are dispersed in Tris-HCl buffer and stored in a 4°C freezer for later use.
[0074] In this step, the amount of doxorubicin added was controlled so that the concentration of doxorubicin in the PNA-NHS nanogel dispersion was 0.5 mg / mL, that is, the mass ratio of doxorubicin to PNA-NHS nanogel was 1:1.
[0075] (3) Preparation of doxorubicin-loaded nanoparticles with multi-responsiveness (PNA-DOX-FA nanoparticles)
[0076] Tris was dissolved in deionized water to prepare a Tris buffer solution with a concentration of 15 mmol / L, and then the pH value thereof was adjusted to 8.2 with dilute hydrochloric acid to obtain a Tris-HCl buffer solution.
[0077] Folic acid-polyethylene glycol-amino (FA-PEG-NH2) was uniformly dispersed in Tris-HCl buffer to obtain a FA-PEG-NH2 dispersion with a concentration of 2.5 mg / mL; PNA-NHS-DOX nanoparticles were dispersed in Tris-HCl buffer to obtain a PNA-NHS-DOX nanoparticle dispersion with a concentration of 2.5 mg / mL. The PNA-NHS-DOX nanoparticle dispersion was added dropwise to the FA-PEG-NH2 dispersion, and the molar ratio of the PNA-NHS nanogel to the FA-PEG-NH2 in the PNA-NHS-DOX nanoparticles was controlled to be 1:1. The reaction was stirred at room temperature in the dark for 24 hours, and then centrifuged at 5000 rpm for 15 minutes using an ultrafiltration tube (MWCO=50 kDa). The obtained solid phase was washed with deionized water for 3 times, freeze-dried, and PNA-DOX-FA was obtained, which was sealed and placed in a drying cabinet for storage.
[0078] Example 2
[0079] In this embodiment, drug-loaded nanoparticles with multiple responsiveness were prepared, and the operation was basically the same as in Example 1, except that: in step (2), a total of 4 experimental groups were set up, and in each experimental group, the amount of doxorubicin added was controlled so that the concentration of doxorubicin in the PNA-NHS nanogel dispersion was 0.25, 1, 1.5, and 2 mg / mL, respectively. That is, in each experimental group, the mass ratio of doxorubicin to PNA-NHS nanogel was 0.5:1, 2:1, 3:1, and 4:1, respectively.
[0080] Comparative Example 1
[0081] In this comparative example, poly(N-isopropylacrylamide-co-acrylic acid) nanoparticles (PNA-DOX nanoparticles) loaded with doxorubicin were prepared by the following steps:
[0082] (1) Preparation of poly (N-isopropylacrylamide-co-acrylic acid) nanogel (PNA nanogel)
[0083] The structure of PNA is shown in formula (IV):
[0084]
[0085] In formula (II), in formula (I), a:b:c=20:1:1.
[0086] ① Add NIPAM monomer, cross-linking agent MBA, SDS and AA monomer into a flat-bottom flask, add deionized water and stir until dissolved to obtain a reaction precursor solution; introduce nitrogen for 30 minutes to remove oxygen in the reaction precursor solution; seal the flat-bottom flask and place it in a 70°C water bath, dissolve the initiator KPS in deionized water, and quickly add the KPS aqueous solution into the flat-bottom flask with a syringe under the condition of introducing nitrogen. When the solution in the flat-bottom flask turns light blue, stop introducing nitrogen, quickly seal the flat-bottom flask, and react at 70°C for 4 hours.
[0087] In this step, in the reaction precursor solution, the concentration of NIPAM monomer is 7.06 mg / mL, the molar ratio of MBA, AA monomers to NIPAM monomer is 1:1:20, the amount of SDS is 5% of the molar amount of NIPAM monomer, and the amount of KPS is 1.47% of the molar amount of NIPAM monomer.
[0088] ② Take the flat-bottom flask out of the water bath, place it in an ice-water mixture to cool to room temperature, filter it with filter paper to remove agglomerates and other impurities, add the filtrate into a dialysis bag (MWCO = 100wDa), and dialyze it in deionized water for 7 days to remove unreacted monomers. During the dialysis process, replace the deionized water twice a day. The dialyzed product is freeze-dried to obtain PNA nanogel.
[0089] (2) Preparation of doxorubicin-loaded poly(N-isopropylacrylamide-co-acrylic acid) nanoparticles (PNA-DOX nanoparticles)
[0090] Tris was dissolved in deionized water to prepare a Tris buffer solution with a concentration of 15 mmol / L, and then the pH value thereof was adjusted to 8.2 with dilute hydrochloric acid to obtain a Tris-HCl buffer solution.
[0091] Add the PNA nanogel to the Tris-HCl buffer, stir thoroughly to evenly disperse the PNA, and obtain a PNA nanogel dispersion with a concentration of 0.5 mg / mL. Add DOX to the PNA nanogel dispersion, stir for 24 hours at room temperature in the dark, then centrifuge at 5000 rpm for 15 minutes using an ultrafiltration tube (MWCO=50 kDa), and wash the resulting solid phase three times with Tris-HCl buffer to obtain PNA-DOX nanoparticles. The resulting PNA-DOX nanoparticles were dispersed in Tris-HCl buffer and stored in a 4°C freezer for later use.
[0092] In this step, the amount of DOX added was controlled so that the concentrations of DOX in the PNA nanogel dispersion were 0.25, 1, 1.5, and 2 mg / mL, respectively, that is, the mass ratio of DOX to PNA nanogel was 1:1, respectively.
[0093] Comparative Example 2
[0094] In this comparative example, PNA-DOX nanoparticles were prepared by the same operation as in comparative example 1, except that: in step (2), a total of 4 experimental groups were set up, and in each experimental group, the amount of DOX added was controlled so that the concentration of DOX in the PNA nanogel dispersion was 0.25, 1, 1.5, and 2 mg / mL, respectively. That is, in each experimental group, the mass ratio of DOX to PNA nanogel was 0.5:1, 2:1, 3:1, and 4:1, respectively.
[0095] Example 3
[0096] In this example, the intermediate products and final products in Example 1 and Comparative Example 1 were characterized.
[0097] 1. Transmission electron microscopy (TEM) test
[0098] The PNA nanogel in Comparative Example 1 and the PNA-DOX-FA nanoparticles in Example 1 were dispersed in deionized water to form a dispersion with a concentration of 0.2 mg / mL. 10 μL of the dispersion was added dropwise to a copper mesh, and the solution on the copper mesh was dried with an infrared lamp to prepare a TEM sample coated with PNA nanogel and a TEM sample coated with PNA-DOX-FA nanoparticles. The morphology of the PNA nanogel and PNA-DOX-FA nanoparticles in the dry state was observed by TEM. The results are as follows: Figure 2 shown.
[0099] Figure 2 Figures a and b are TEM images of PNA nanogel and PNA-DOX-FA nanoparticles in dry state. Figure 2 It can be seen that the diameter of PNA nanogel is between 50 and 100 nm, and the diameter of PNA-DOX-FA nanogel is slightly larger than that of PNA nanogel.
[0100] 2. Hydraulic diameter and diameter distribution test
[0101] The PNA nanogel in Comparative Example 1 and the PNA-DOX-FA nanoparticles in Example 1 were freeze-dried and then dispersed in deionized water, pH 5.5 and pH 7.4 PBS buffers to form dispersions with a concentration of 0.5 mg / mL. The hydrodynamic diameter and diameter distribution test was performed using a dynamic light scattering (DLS) instrument, the scattering angle of the test was set to 90°C, the test temperature was set to 25°C, the test was repeated 3 times, and the test result was the average of the 3 measurements.
[0102] The diameter distributions of PNA nanogels and PNA-DOX-FA nanoparticles in deionized water, pH 5.5, and pH 7.4 PBS buffers are shown in Figure 2. Figure 3 As shown by Figure 3 It can be seen that the diameter of PNA-DOX-FA nanoparticles is larger than that of PNA nanogels.
[0103] 3. Infrared spectrum test
[0104] The infrared spectra of the PNA nanogel and PNA-DOX nanoparticles in Comparative Example 1, and the PNA-DOX-FA nanoparticles and FA-PEG-NH2 in Example 1 were tested. The results are as follows: Figure 4 As shown. At 1367cm -1 and 1387cm -1 The symmetrical in-plane bending vibration peak of the methyl group in the isopropyl group (-CH(CH3)2) appears near 1638cm -1 The characteristic absorption peaks of carbonyl stretching vibration in the amide bond (CO-NH) appear at 1711 cm -1 The characteristic absorption peak of carboxyl (C=O) stretching vibration appears at 1112 cm, which is the characteristic group of acrylic acid. This indicates that acrylic acid was successfully introduced into the gel network of PNIPAM by precipitation copolymerization. -1 The infrared characteristic absorption peak of PEG ether bond (COC) is shown at the bottom, which indicates that the long chain of FA-PEG-NH2 is successfully grafted onto the surface of nanoparticles.
[0105] 4. Ultraviolet-visible spectrum (UV-vis) test
[0106] DOX, the PNA nanogel and PNA-DOX nanoparticles in Comparative Example 1, and the PNA-DOX-FA nanoparticles and FA-PEG-NH2 in Example 1 were dissolved or dispersed in deionized water, and then the absorbance curve of each sample in the range of 200 to 800 nm was tested. The results are as follows: Figure 5 As shown. Figure 5It can be seen that DOX was successfully loaded into PNA-DOX nanoparticles and PNA-DOX-FA nanoparticles.
[0107] 5. 1 H NMR testing
[0108] The FA-PEG-NH2, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles in Example 1 were tested. 1 HNMR spectrum, DMSO-d6 was used as solvent and the test frequency was 400Hz. Figure 6 shown. Figure 6 The curves (a), (b), and (c) are respectively FA-PEG-NH2, PNA-NHS-DOX, and PNA-DOX-FA. 1 H NMR spectrum. The FA-PEG-NH2 molecular chain has obvious characteristic peaks of PEG (3.51ppm, -OCH 2- CH2O-), PNA-DOX nanoparticles have obvious characteristic peaks of PNIPAM (1.09ppm, -CH(CH3)2). After grafting FA-PEG-NH2, PNA-DOX-FA nanoparticles simultaneously show characteristic peaks of PNIPAM (1.09ppm, -CH(CH3)2) and PEG (3.63ppm, -OCH2CH2O-), indicating that FA-PEG-NH2 was successfully grafted onto the surface of PNA-DOX nanoparticles.
[0109] 6.X-ray Photoelectron Spectroscopy (XPS) Test
[0110] XPS was used to analyze the surface element contents of the PNA nanogel and PNA-DOX nanoparticles in Comparative Example 1 and the PNA-DOX-FA nanoparticles in Example 1. The results are shown in Table 1.
[0111] Table 1 XPS element content test results
[0112]
[0113] Example 4
[0114] In this example, the stability of the PNA nanogel prepared in Comparative Example 1 and the PNA-DOX-FA nanoparticles prepared in Example 1 were tested.
[0115] The PNA nanogel prepared in Comparative Example 1 and the PNA-DOX-FA nanoparticles prepared in Example 1 were freeze-dried and then dispersed in a PBS buffer solution at pH 7.4 and a cell culture medium containing 10% FBS, respectively, to form a dispersion solution with a concentration of 0.5 mg / mL. The hydrodynamic diameter and Zeta potential analysis were performed daily using DLS for a total of 7 days, with the scattering angle of the test set at 90°C and the test temperature set at 25°C. The test was performed 3 times, and the test results were taken as the average of the 3 measurements.
[0116] Figure 7 is the zeta potential of PNA-DOX-FA nanoparticles in deionized water, PBS buffer at pH 5.5, PBS buffer at pH 7.4, and cell culture medium (Medium) containing 10% FBS. Figure 8 The hydrodynamic diameter and Zeta potential of PNA nanogel and PNA-DOX-FA gel particles in PBS buffer at pH 7.4 and cell culture medium containing 10% FBS change over time, where a and b represent PNA nanogel, and c and d represent PNA-DOX-FA nanoparticles. Figure 8 It can be seen that the particle diameter and Zeta potential of PNA nanogel and PNA-DOX-FA nanoparticles remained basically unchanged in PBS buffer at pH 7.4 and cell culture medium containing 10% FBS for 7 days, indicating that both have excellent stability in PBS buffer at pH 7.4 and cell culture medium containing 10% FBS.
[0117] Example 5
[0118] In this example, the temperature and pH response properties of the intermediate product and the final product in Comparative Example 1 and Example 1 were tested.
[0119] (1) The PNA nanogel and PNA-DOX nanoparticles prepared in Comparative Example 1, and the PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles prepared in Example 1 were freeze-dried and dispersed in deionized water to form a dispersion with a concentration of 0.5 mg / mL. The hydrodynamic diameter test was performed using DLS, the scattering angle of the test was set to 90°C, the test temperature range was 21-59°C, the hydrodynamic diameter was measured every 2°C, each temperature point was balanced for 6 minutes, each temperature point was tested 3 times, and the test result was the average of 3 measurements.
[0120] Fig. 9 The curves of the hydrodynamic diameter of PNA nanogel, PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles in deionized water as a function of temperature are shown in Figure 2. Fig. 9It can be seen that PNA nanogels, PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles all have temperature-sensitive properties, and their diameters decrease with increasing temperature.
[0121] (2) The PNA nanogel and PNA-DOX nanoparticles prepared in Comparative Example 1, the PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles prepared in Example 1 were freeze-dried and dispersed in a pH 5.5 PBS buffer, a pH 7.4 PBS buffer, and a cell culture medium containing 10% FBS, respectively, to form a dispersion with a concentration of 0.5 mg / mL. The hydrodynamic diameter test was performed using DLS, the scattering angle of the test was set to 90°C, the test temperature range was 21-59°C, the hydrodynamic diameter was measured every 2°C, each temperature point was balanced for 6 minutes, each temperature point was tested 3 times, and the test result was the average of the 3 measurements.
[0122] Fig.10 The curves of the hydrodynamic diameter of PNA nanogel, PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles in PBS buffer at pH 5.5 and pH 7.4 and cell culture medium containing 10% FBS as a function of temperature are shown in FIG. Fig.10 It can be seen that PNA nanogels, PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles have pH responsiveness and temperature responsiveness.
[0123] Example 6
[0124] DOX is a broad-spectrum antitumor antibiotic that has a killing effect on various tumor cells by inhibiting the synthesis of nucleic acid, the genetic material of tumor cells. In this example, DOX was used as a model drug to test and evaluate the drug loading, drug encapsulation efficiency and drug release behavior of the PNA-DOX nanoparticles prepared in Comparative Example 1 and the PNA-DOX-FA nanoparticles prepared in Example 1.
[0125] (1) Establishment of DOX standard curve: Dissolve DOX in water to prepare a series of DOX standard solutions with DOX concentrations ranging from 10 to 50 μg / mL. Determine the absorbance of the DOX standard solution at a wavelength of 480 nm by UV-vis and draw a DOX standard curve, such as Fig.11 shown.
[0126] (2) The absorbance value of the washing solution of the PNA-DOX-FA nanoparticles during the preparation process at a wavelength of 480 nm was measured by UV-vis, and the concentration of DOX in the washing solution was calculated using the DOX standard curve. The drug loading (LC) and embedding efficiency (EE) of the PNA-DOX-FA nanoparticles prepared under different DOX concentration conditions (when the concentration of doxorubicin in the PNA-NHS nanogel dispersion was 0.25, 0.5, 1, 1.5, and 2 mg / mL in step (2) of Example 1 and Example 2 were respectively calculated. The calculation formula is shown in formulas (1) to (2):
[0127]
[0128]
[0129] The encapsulation efficiency and drug loading test results of PNA-DOX-FA prepared at different DOX concentrations are shown in Fig.12 As shown by Fig.12 It can be seen that when the concentration of doxorubicin in the PNA-NHS nanogel dispersion is 0.25, 0.5, 1, 1.5, and 2 mg / mL, respectively, the embedding rate of the prepared PNA-DOX-FA nanoparticles is about 90%, and the drug loading amount shows a trend of gradually increasing.
[0130] (3) Dynamic dialysis was used to investigate the drug release behavior of PNA-DOX nanoparticles and PNA-DOX-FA nanoparticles
[0131] PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles were dispersed in deionized water to form a dispersion with a nanoparticle concentration of 5 mg / mL. 1 mL of each dispersion was taken and added to a dialysis bag (MWCO = 100 wDa), and placed in a jacketed beaker containing 200 mL of PBS buffer at pH 5.5 and pH 7.4 and containing 150 mmol / L NaCl. Circulating water at 25°C, 37°C and 42°C was passed into the jacketed beaker, respectively, and the drug was released at a stirring speed of 400 rpm. At a specific time point, 20 mL of the dialysate was taken out and supplemented with 20 mL of the corresponding fresh PBS buffer. The concentration of DOX in the dialysate was detected by UV-vis. The cumulative release rate (CR) of DOX was calculated according to formula (3):
[0132]
[0133] In formula (3), V0 is the total volume of the release medium (V0 = 200 mL in this step); C iis the concentration of DOX in the release medium taken out for the ith time (mg / mL), V is the volume of the dialysate taken out each time (V=20 mL in this step), and M is the total amount of DOX (mg).
[0134] Fig.13 The drug release curves of PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles in PBS buffer at different pH values and temperatures, where a, b and c represent PNA-DOX nanoparticles, PNA-NHS-DOX nanoparticles and PNA-DOX-FA nanoparticles, respectively. Fig.12 It can be seen that within 48 hours of the test, PNA-DOX, PNA-NHS-DOX and PNA-DOX-FA had higher cumulative DOX release rates at pH 5.5 compared with those at pH 7.4. At the same time, the cumulative DOX release rates of PNA-DOX, PNA-NHS-DOX and PNA-DOX-FA increased with increasing temperature.
[0135] Example 7
[0136] In this example, the live-dead cell staining method was used to examine the cytotoxicity of the PNA-DOX-FA nanoparticles in Example 1.
[0137] (1) Take L929, Hela and 4T1 cells in the logarithmic growth phase and digest them with trypsin / EDTA (2.5%) to prepare a single cell suspension. Inoculate the cell suspension in a 12-well plate with 1 mL per well at a cell density of 5×10 4 The cells were placed in a constant temperature cell culture incubator at 5% CO2 and 37°C for 24 h.
[0138] (2) The original culture medium was discarded and 1 mL of culture medium containing different concentrations (1, 10, 50, 100, 200, 400 μg / mL) of PNA-DOX-FA nanoparticles was added to each well and culture was continued for 72 h.
[0139] (3) Discard the original culture medium, wash the cells three times with PBS buffer, add 1 mL of the pre-prepared acetoxymethyl ester-introduced calcein (Calcein-AM) / propidium iodide (PI) double staining working solution (Calcein-AM concentration is 2 μmol / L, PI concentration is 4.5 μmol / L), stain at 37°C for 15 min, wash the cells twice with PBS buffer, and observe and photograph them using a fluorescence microscope.
[0140] Fig.14The fluorescence images of different concentrations of PNA-DOX-FA nanoparticles co-cultured with L929, Hela and 4T1 cells for 72 hours are shown in Figure 2. Fig.14 It can be seen that after co-culture of PNA-DOX-FA nanoparticles with L929, Hela and 4T1 cells for 72 hours, the growth of L929, Hela and 4T1 cells was very good and no death occurred, indicating that the growth of cells was not inhibited, indicating that PNA-DOX-FA nanoparticles have excellent biocompatibility.
[0141] Example 8
[0142] In this example, the difference in the uptake of the PNA-DOX nanoparticles of Comparative Example 1 and the PNA-DOX-FA nanoparticles of Example 1 by cells was investigated.
[0143] 4T1 cells were cultured at 2×10 4 The cells were inoculated at a density of 1000 / well in a confocal culture dish and cultured in a constant temperature cell culture incubator at 5% CO2 and 37°C. After culturing for 24 hours, the original culture medium was discarded and complete culture medium containing DOX, PNA-DOX nanoparticles or PNA-DOX-FA nanoparticles was added respectively, and the culture was continued for 3 hours to control the relative concentration of DOX to 5 μg / mL. After the culture was completed, the culture medium was discarded and the cells were washed twice with PBS buffer. Then, the cells were fixed with 4% paraformaldehyde at 37°C for 15 minutes and then washed twice with PBS buffer. Then, the cell nucleus was stained with 1 μg / mL of 4',6-diamidino-2-phenylindole (DAPI) at 37°C for 10 minutes and the cells were washed twice with PBS buffer. Finally, CLSM was used to observe and photograph. Fig.15 This is the CLSM image of 4T1 cells co-cultured with DOX, PNA-DOX nanoparticles and PNA-DOXFA nanoparticles for 3 hours. It can be clearly seen from the figure that the fluorescence intensity of PNA-DOX-FA nanoparticles with a folic acid layer is stronger than that of PNA-DOX nanoparticles after 3 hours of culture, which indicates that the cells will take up more PNA-DOX-FA nanoparticles, and the introduction of the folic acid layer can enhance the targeting ability of the nanoparticles.
[0144] Example 9
[0145] In this example, the effects of PNA-DOX nanoparticles and PNA-DOX-FA nanoparticles on the cell activity of different cancer cells were tested. Specifically, the CCK-8 method was used to investigate the inhibitory effects of PNA-DOX nanoparticles and PNA-DOX-FA nanoparticles at different concentrations (0.01, 0.02, 0.1, 0.2, 0.5, 1, 2, 4 μg / mL) on different cancer cells (4T1, A549, Hep-G2, Hela cells).
[0146] (1) 4T1, A549, Hep-G2 and Hela cells were seeded at a density of 5000 cells / well in a 96-well plate and cultured in a constant temperature cell culture incubator at 5% CO2 and 37°C for 24 h.
[0147] (2) The original culture medium was discarded, and 100 μL of complete culture medium containing different concentrations of nanoparticles (PNA-DOX nanoparticles or PNA-DOX-FA nanoparticles) was added to each well and cultured for 24 h, 48 h, and 72 h as the experimental group; complete culture medium without nanoparticles was added to the control group; no cells and nanoparticles were added to the blank group.
[0148] (3) After culturing for 72 h, the original culture medium was discarded and 100 μL of complete culture medium containing CCK-8 was added, and the culture was continued for 4 h, wherein the concentration of CCK-8 was 10 μL / 100 μL.
[0149] (4) Use an ELISA reader to measure the absorbance of the well plate at a wavelength of 450 nm. Five parallel experiments are set up for the experimental group, control group and blank group, and the final absorbance value is the average of the five parallel experiments. Calculate the cell activity according to formula (4):
[0150]
[0151] In formula (4), A s is the absorbance value of the experimental group, A c is the absorbance value of the control group, A b is the absorbance value of the blank group.
[0152] Fig.16 The results of the test on the inhibitory effects of different concentrations of PNA-DOX nanoparticles and PNA-DOX-FA nanoparticles on different tumor cells are shown in Figure 2. Fig.16 It can be seen that at the same concentration and the same action time, PNA-DOX-FA nanoparticles have stronger killing effects on 4T1, A549, Hep-G2 and Hela cells than PNA-DOX nanoparticles.
Claims
1. Targeted drug-loaded nanoparticles with multiple responsiveness, characterized in that: The targeted drug-loaded nanoparticles are composed of a poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel with temperature and pH response characteristics, an antitumor drug, and a folic acid layer that can specifically target the folate receptor of tumor cells; the antitumor drug is loaded in the polymer network structure of the nanogel to form drug-loaded nanoparticles, the folic acid layer is composed of aminated folic acid molecules, the folic acid layer coats the drug-loaded nanoparticles, and the amino groups of the aminated folic acid molecules are grafted on the surface of the drug-loaded nanoparticles; the antitumor drug is a hydrophilic or / and positively charged drug; the structure of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) is as shown in formula (I), In formula (I), a:b:c:b1=(18~20):(0.8~1.2):(0.8~1.2):(0.8~1.2), a1:b1:c1=(18~20):(0.8~1.2):(0.8~1.2).
2. The multi-responsive targeted drug-loaded nanoparticles according to claim 1, characterized in that: The aminated folic acid molecule is a folic acid-polyethylene glycol-amino group having a structure as shown in formula (II) or a folic acid-fat chain-amino group having a structure as shown in formula (III).
3. The multi-responsive targeted drug-loaded nanoparticles according to claim 1, characterized in that: In the targeted drug-loaded nanoparticles, the molar ratio of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel to the folic acid layer is 1:(0.8-1.2).
4. The targeted drug-loaded nanoparticle with multi-responsiveness according to any one of claims 1 to 3, characterized in that: The diameter of the targeted drug-loaded nanoparticles in a dry state is 50 to 200 nm.
5. The targeted drug-loaded nanoparticle with multi-responsiveness according to any one of claims 1 to 3, characterized in that: The anti-tumor drug is combined in the polymer network structure of the nanogel through electrostatic action.
6. The method for preparing the targeted drug-loaded nanoparticles with multi-responsiveness according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of drug-loaded nanoparticles The poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is added to a Tris-HCl buffer having a pH value of 8.0 to 8.5, and then an anti-tumor drug is added, and the mixture is fully stirred at room temperature to load the anti-tumor drug into the polymer network of the nanogel, and the mixture is centrifuged, and the obtained solid phase is washed to obtain drug-loaded nanoparticles; The structure of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is shown in formula (I). In formula (I), a:b:c:b1=(18-20):(0.8-1.2):(0.8-1.2):(0.8-1.2), a1:b1:c1=(18-20):(0.8-1.2):(0.8-1.2); (2) Preparation of drug-loaded nanoparticles coated with folic acid The aminated folic acid molecules are fully dispersed in a Tris-HCl buffer with a pH value of 8.0 to 8.5 to obtain an aminated folic acid molecule dispersion; the drug-loaded nanoparticles are fully dispersed in a Tris-HCl buffer with a pH value of 8.0 to 8.5 to obtain a drug-loaded nanoparticle dispersion; the drug-loaded nanoparticle dispersion is added dropwise to the aminated folic acid molecule dispersion, fully reacted at room temperature, protected from light and stirred, centrifuged, and the obtained solid phase is washed to obtain the product.
7. The method for preparing targeted drug-loaded nanoparticles with multi-responsiveness according to claim 6, characterized in that: In step (2), the drug-loaded nanoparticle dispersion is added dropwise to the aminated folic acid molecule dispersion in a ratio of 1:(0.8-1.2) of the molar amount of the drug-loaded nanoparticles to the aminated folic acid molecules.
8. The method for preparing targeted drug-loaded nanoparticles with multi-responsiveness according to claim 7, characterized in that: In step (2), the concentration of the drug-loaded nanoparticle dispersion is 1 to 10 mg / mL, and the concentration of the amino-modified folic acid molecule dispersion is 1 to 10 mg / mL.
9. The method for preparing targeted drug-loaded nanoparticles with multi-responsiveness according to any one of claims 6 to 8, characterized in that: Step (1) adding poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel to a dispersion formed in a Tris-HCl buffer having a pH value of 8.0 to 8.5, wherein the concentration of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is 1 to 10 mg / mL.
10. The method for preparing targeted drug-loaded nanoparticles with multi-responsiveness according to any one of claims 6 to 8, characterized in that: The preparation method of the poly(N-isopropylacrylamide-co-acrylic acid-co-N-acryloyloxysuccinimide) nanogel is as follows: ① Dissolve N-isopropylacrylamide monomer, crosslinking agent N,N'-methylenebisacrylamide, acrylic acid monomer, N-acryloyloxysuccinimide monomer and sodium dodecyl sulfate in water to obtain a reaction precursor solution; after removing oxygen from the reaction precursor solution, add a thermal initiator and react at 70-80°C for 3-4 hours under nitrogen protection; In the reaction precursor solution of this step, the concentration of N-isopropylacrylamide monomer is 5-10 mg / mL, the molar ratio of the crosslinking agent, acrylic acid monomer, N-acryloxysuccinimide monomer and N-isopropylacrylamide monomer is (0.8-1.2):(0.8-1):(0.8-1):(0.8-1), the amount of sodium dodecyl sulfate is 3%-5% of the molar amount of N-isopropylacrylamide monomer, and the amount of the thermal initiator is 1%-3% of the molar amount of N-isopropylacrylamide monomer; ② Filter the obtained reaction solution, add the filtrate into a dialysis bag, place it in water for sufficient dialysis, and freeze-dry to obtain.
Citation Information
Cited By
Metal coordination nucleic acid polypeptide targeted delivery nanoparticle and preparation method thereof
CN121243344A
Composite nanogel as well as preparation method and application thereof
CN121466351A